Increasing value and reducing waste in data extraction for systematic reviews: tracking data in data extraction forms - Shokraneh, Farhad; Adams, Clive E. (BioMed Central, 2017)
Data extraction is one of the most time-consuming tasks in performing a systematic review. Extraction is often onto some sort of form. Sharing completed forms can be used to check quality and accuracy of extraction or for re-cycling data to other researchers for updating. However, validating each piece of extracted data is time-consuming and linking to source problematic. In this methodology paper, we summarize three methods for reporting the location of data in original full-text reports, comparing their advantages and disadvantages.